Adipose stromal vascular fraction cell sheets as vascular strategies for tissue engineering and regenerative medicine applications - Costa, Marina Filipa da Silva (2015)
Tese de mestrado em Engenharia Biomédica e Biofísica, apresentada à Universidade de Lisboa, através da Faculdade de Ciências, 2015